THE EFFECT OF DEMONSTRATION LEARNING METHODS ON MATHEMATICS LEARNING ACHIEVEMENT OF ELEMENTARY SCHOOL STUDENTS - Putri, Faza Tsaniya (DIRASATUL IBTIDAIYAH, 2023)
The purpose of this study was to elaborate the effect of demonstration learning methods on mathematics learning achievement of elementary school students. The research method used in this study is the Systematic Literature Review (SLR) method. The material point to be discussed is the demonstration method in influencing student achievement, because one of the factors that can increase student achievement is the selection of methods applied by teachers to learning. This demonstration method in learning involves an object using learning media to demonstrate a process or action, either directly or indirectly which aims to clarify concepts that are in accordance with the learning material so that students are more active in learning activities.